2022
DOI: 10.1161/circresaha.122.321055
|View full text |Cite
|
Sign up to set email alerts
|

Blocking MG53 S255 Phosphorylation Protects Diabetic Heart From Ischemic Injury

Abstract: BACKGROUND: As an integral component of cell membrane repair machinery, MG53 (mitsugumin 53) is important for cardioprotection induced by ischemia preconditioning and postconditioning. However, it also impairs insulin signaling via its E3 ligase activity-mediated ubiquitination-dependent degradation of IR (insulin receptor) and IRS1 (insulin receptor substrate 1) and its myokine function-induced allosteric blockage of IR. Here, we sought to develop MG53 into a cardioprotection therapy by separating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In summary, the study by Lv et al 14 provides new insights into how MG53 targets protein substrates for ubiquitination. In diabetic heart, GSK3-dependent phosphorylation of MG53 at Serine 255 increases MG53 recognition, ubiquitination, and degradation of critical insulin signaling pathway proteins, contributing to insulin resistance and increased susceptibility to ischemic injury.…”
Section: Article See P 962mentioning
confidence: 95%
See 1 more Smart Citation
“…In summary, the study by Lv et al 14 provides new insights into how MG53 targets protein substrates for ubiquitination. In diabetic heart, GSK3-dependent phosphorylation of MG53 at Serine 255 increases MG53 recognition, ubiquitination, and degradation of critical insulin signaling pathway proteins, contributing to insulin resistance and increased susceptibility to ischemic injury.…”
Section: Article See P 962mentioning
confidence: 95%
“…In this issue, Lv et al 14 extended their findings into MG53 ligase function by exploring whether endogenous kinases act to shift the balance between MG53 substrate ubiquitination and membrane healing activities (Figure). By performing mass spectrometry analysis on MG53 immunoprecipitated from skeletal myocytes and heterologously expressing HEK cells, the residue Serine 255 was found to be phosphorylated in both groups and among 5 phosphosites in the muscle expressed protein.…”
Section: Article See P 962mentioning
confidence: 99%
“…In particular, GSK3β is a kinase required for high glucose-induced serine332 phosphorylation, ubiquitination, and degradation of IRS1. 29 Likewise, GSK3βenhanced phosphorylation of MG53 enables its E3 ligase activity to mediate the degradation of both IR and IRS1, 30 which may partly account for the involvement of GSK3β in insulin resistance. Moreover, Chunyi et al revealed that augmented GSK3β phosphorylation elevates AKT signaling in breast cancer.…”
Section: And Different Cellular Signaling Pathwaysmentioning
confidence: 99%
“…For instance, investigations have successfully attenuated insulin resistance induced by MG53 through targeted disruption of the interaction between MG53 and IRS-1 (Lee et al, 2016). The MG53 mutant currently under construction exhibits the ability to circumvent its E3 ubiquitin ligase activity (Lv et al, 2022), thereby offering a novel therapeutic approach for diabetes, muscle injury diseases, and cardiovascular disorders.…”
Section: Mg53 Can Cause Metabolic Syndromementioning
confidence: 99%
“…On this basis, efforts should be made to preserve the anti-tumor therapeutic ability of MG53 while mitigating its side effects. Currently, MG53 mutants, which retain membrane repair function without compromising glucose metabolism, have been developed by eliminating the E3 ubiquitin ligase properties of MG53 (Lv et al, 2022). However, in the context of cancer treatment, the E3 ubiquitin ligase of MG53 appears to play a pivotal role.…”
Section: Optimizing the Anti-tumor Effect Of Mg53: Harnessing E3 Ubiq...mentioning
confidence: 99%